A Scoping Review of Barriers and Facilitators Affecting the Lives of People With Disabilities During COVID-19 - Croft, Samantha; Fraser, Sarah (Frontiers in Rehabilitation Sciences, 2022)
Purpose: This scoping review aimed to identify the barriers and facilitators to everyday activities and social participation of people with a disability (PWD) during the first wave of the COVID-19 pandemic. Methods: The search terms (disability and COVID-19) were used in four databases: CINAHL, Medline (Ovid), EMBASE and Web of Science. The search conducted from January 2019 to September 22, 2020, identified 465 peer reviewed articles and abstracts and were screened in Covidence software. Studies were included if they had the terms “covid-19” and “disability”, were published in English, and specifically examined how COVID-19 impacted the daily lives of PWD. Exclusion criteria included: disability as a symptom or result of COVID-19, the health outcomes when PWD acquired COVID-19, disability leave for someone who is sick and the risk of acquiring the disease for PWD. 74 articles met the inclusion criteria and were analyzed via data charting. Charting began with existing barriers and facilitators identified by the World Health Organization and new barriers and facilitators, that emerged from the texts were added during this process. Results: The barriers that emerged included: access to information, ease of communication, financial impacts, mental health impacts, access to essential services, physical safety, educational challenges, and changes to care and rehabilitation. Significant facilitators included: changes to care and rehabilitation, new innovations, social and familial support and inclusive policy measures. Conclusions: COVID-19 exacerbated existing challenges in the lives of PWD and raised new quality of life concerns. Findings also demonstrate that policy makers, health care professionals and others continually support PWD in times of crisis.